Ketika Tafsir Menjadi Alat Kekuasaan: Studi Atas Ayat- Ayat Politik - mohammad, komarudin; ahmad, kafiy; alfaruq, salman; khoir, atfhan (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2025)
This research examines the phenomenon of Quranic interpretation, positioned as a tool of power in the political realm, particularly through the interpretation of political verses. Interpretation, which should be a means of spiritual and moral understanding, has historically often become an instrument of legitimacy for certain regimes or groups. The research uses qualitative methods with a library research approach, examining various works on Quranic interpretation and related literature on the relationship between interpretation and politics, both in classical and contemporary periods, focusing on the case of Indonesia. The results show that Quranic interpretation is often used by those in power to strengthen policy legitimacy, reinforce ideological narratives, and even restrict divergent religious expressions. Interpretation becomes a field for contestation of meaning between diverse political and religious groups, making it vulnerable to bias and potentially leading to social polarization. This study highlights the strong influence of power on the construction of meaning in interpretation, making religious interpretation vulnerable to monopolization and misuse for the pragmatic interests of those in power. This study also emphasizes the need to develop critical, inclusive interpretations free from the intervention of those in power, so that interpretation maintains its function as a moral and ethical enlightener, rather than simply a tool for political propaganda. This research is expected to foster critical awareness in understanding the interpretation and contextualization of political verses, for the sake of a more just and democratic harmony in religious and national life.